The prevalence of developmental coordination disorder in school going children of west india (Funded Work) - DR. SANJIVANI N DHOTE (PT); DR. MANISHARATHI (PHD); DR. TUSHARPALEKAR (PH.D) (International Journal of Pharma and Bio Sciences, 2017)
Development specifies maturation of functions. It is related to the maturation and myelination of the nervous system and indicates acquisition of a variety of skills for optimal functioning of the individual.1Considering the importance of timely diagnosis of DCD andthe child’s performance on the BOT-2 will allow the physical therapist to identify areas of strength and areas of need in regards to the child’s gross motor functioning, and can therefore help to guide treatment.The early diagnosis of DCD can be helpful to prevent the future secondary complications. So purpose of this study is to find out the prevalence of DCD on BOT-2 in 5 to 15 years school going children. : It was a cross-sectional analytical study conducted in schools of Pimpri-Chinchwad area. This study included 516 students assessed by Using BOT-2nd edition. Prevalence of DCD was 1.16% (95%CI 0.43% to 2.51%). Where as female showed more prevalence of Developmental coordination disorder than Male